A wideband metamaterial absorber based on a magnetic resonator loaded with lumped resistors - 程用志 龚荣洲 聂彦 王鲜 (Chinese physics B, 2012)
A wideband metamaterial absorber （MA） based on a magnetic resonator loaded with lumped resistors is presented. It is composed of a one-dimensional periodic array of double U-shaped structured magnetic resonators loaded with lumped resistors, a dielectric substrate, and a metal plate. We simulated, fabricated, measured, and analyzed the MA. The experimental results show that the reflectance （S11） is below -10 dB at normal incidence in the frequency range of 7.7 GHz 18 GHz, and the peak value is about -20 dB. Simulated power loss density distributions indicate that wideband absorption of the MA is mainly attributable to the lumped resistors in the magnetic resonator. Further investigations indicate that the distance between two unit cells along the magnetic field direction significantly influences the performance of the MA.